UPAYA MENINGKATKAN KEMAMPUAN BERPIDATO DENGAN MEDIA AUDIO VISUAL PEMBELAJARAN BAHASA INDONESIA KELAS VI SD - AHMAD KORI (Lembaga Penelitian dan Studi kebijakan MADANI Instutute, 2013)
The problems to be examined in this study are : ( a) How does an increase in student achievement and influence teaching model Learning Model Application by using audio-visual media in learning Indonesian in Class VI SDN 15 Morning East Cengkareng West Jakarta on motivation and student learning outcomes ? The results of this study show that : The ability of teachers in selecting , using and modifying media with methods / techniques greatly affect the ability of the student speech . The results can be seen in the ability of the student speech enhancement speech ability students in each cycle . In the first cycle of learning with the use of audio- visual media ( VCD ) plus a concrete example of the teacher as a model of engineering practice individually addressed with an integrated learning on aspects of reading and listening to the results obtained 5 students ( 16.67 % ) who scored 75 or more with the average value overall average 55.55 . In the second cycle of learning with the use of audio- visual media ( VCD ) is supported by the media microphone , coupled with the techniques practiced in the group obtained the results of 13 students ( 43.33 % ) who scored 75 or more and the overall average value of 67.37 . In the learning cycle still using audio-visual media ( VCD ) coupled with listening to speech recordings and integrated learning students with aspects of listening , writing , and speaking , modified by the method and discuss the results obtained in the group practice 21 students ( 70 % ) who scored 75 or more and the overall average value of 73.42 . Based on assessment data from student speech capabilities it can be concluded that the learning speech using audio- visual media ( VCD ) can assist students in an effort to improve the ability of speech